2022
DOI: 10.1158/1078-0432.ccr-22-2108
|View full text |Cite
|
Sign up to set email alerts
|

A Novel B7-H6–Targeted IgG-Like T Cell–Engaging Antibody for the Treatment of Gastrointestinal Tumors

Abstract: Purpose: Advanced stage gastrointestinal cancers represent a high unmet need requiring new effective therapies. We investigated the anti-tumor activity of a novel T-cell engaging antibody (B7-H6/CD3 ITE) targeting B7-H6, a tumor-associated antigen that is expressed in gastrointestinal tumors. Experimental Design: Membrane proteomics and immunohistochemistry analysis identified B7-H6 as tumor- associated antigen in gastrointestinal tumor tissues with no to very little expression in normal tissues. The anti-tumo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…The liver is the most frequently affected organ by hematogenous metastases of gastric cancer tumors, after liver metastasis, the survival rate was only 20% ( 3 ) The development of neoadjuvant chemotherapy and immunotherapy for gastric cancer treatment in recent years has led to improvements in the diagnosis and prognosis of gastric cancer to a certain extent, yet further improvement is still necessary ( 4 ). To this end, new tumor markers, therapeutic targets, and treatment strategies need to be developed ( 5 ). Previous studies have shown that the occurrence, proliferation, and metastasis of tumors are closely related to their microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…The liver is the most frequently affected organ by hematogenous metastases of gastric cancer tumors, after liver metastasis, the survival rate was only 20% ( 3 ) The development of neoadjuvant chemotherapy and immunotherapy for gastric cancer treatment in recent years has led to improvements in the diagnosis and prognosis of gastric cancer to a certain extent, yet further improvement is still necessary ( 4 ). To this end, new tumor markers, therapeutic targets, and treatment strategies need to be developed ( 5 ). Previous studies have shown that the occurrence, proliferation, and metastasis of tumors are closely related to their microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…132 However, other studies showed B7-H6 expression was detected in 33/43 of GC cases (77%) and a novel T cell-engaging antibody (B7-H6/CD3 ITE) targeting B7-H6 induced T cell-redirected lysis of tumor cells and recruitment of T cells into noninflamed tumor tissues. 133 A significant correlation between B7-H6 expression levels and OS rate has been found. 62 Thus, additional studies are necessary for clarity on the effects of B7-H6 on GC.…”
Section: B7-h5 (Vista)mentioning
confidence: 93%
“…Additionally, B7‐H6 expression was observed in only a few samples, indicating that it lacks utility as a prognostic marker for GC, and B7‐H6 expression did not influence the prognosis of patients with GC 132 . However, other studies showed B7‐H6 expression was detected in 33/43 of GC cases (77%) and a novel T cell–engaging antibody (B7‐H6/CD3 ITE) targeting B7‐H6 induced T cell–redirected lysis of tumor cells and recruitment of T cells into noninflamed tumor tissues 133 . A significant correlation between B7‐H6 expression levels and OS rate has been found 62 …”
Section: Gastric Precancerous Lesions and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…6 Clinical meanings and functions of B7-H6 in gliomas B7 homolog 6 (B7-H6), also called NCR3LG1, is a kind of the immune checkpoints of the B7 family and plays the role of an endogenous/co-stimulatory ligand. This gene encodes a 454-aalong type I transmembrane protein of which the predicted molecular mass is 51 kDa (93). The B7-H6 extracellular region contains both an IgV-like and an IgC-like domain.…”
Section: Clinical Meanings and Functions Of B7-h4 In Gliomasmentioning
confidence: 99%